MINANGKABAU CLERGIES AND THE WRITING OF HADITH - Jannatul Husna bin Ali Nuar (Jurnal Ushuluddin, 2016)
As one of the barns in the Islamic scholars throughout Indonesian archipelago, many Minangkabau scientists in the field of hadith had born figures spelled out with no exception. Trend of works by scholars of Minang in the field of hadith had also shown its own special evidences. Not only the work of translation and Sharh were generated, but also the original works in the field of hadith even drafted in Arabic. The main purpose of this article is to introduce a number of works on hadith and the science of hadith generated by the egg heads of Minangkabau, typically in the 20th century. As for example, Professor Mahmud Yunus, Engku Mudo Zainuddin Hamidy, Ustaz Fachruddin Husain Datuk Majo Indo, Professor Zainal Abidin Ahmad, Buya Mawardi and Ustaz Muhammad Oemar Bakry Besar Datuk Tan. This study inspired cutting-edge scholars, even if they were graduates of local Surau and Madrasah, glorious hadith’s books of high-value compilation were published similar to the context of riwayah-dirayah hadith, fiqh al-hadith or mushthalah hadith. The works were worthy triggers the spirit and inspiration of Muslim intellectuals today for innovation and transformation. In addition, the recent Muslim intellectual were exposed to a lot of formal higher education and academic degree holders, to be more productive in the delivering of similar treasury with the supports of sophisticated modern technology. Above all, the triggers should have been for the sake of preserving the writings of hadith in this beloved country